Accelerating talent development for the next leader: lesson learned from Dompet Dhuafa / Asep Sapa’at - Sapa’at, Asep (Center for Islamic Philantrophy & Social Finance (CIPSF), 2024)
This research illustrates the importance of a leadership-based professional development program known as the "Leadership Enhancement and Advancement Program" (LEAP) in the context of the non-profit organization Dompet Dhuafa. The LEAP program is designed to develop competencies and train leadership skills of Dompet Dhuafa employees. The research method used in this study is qualitative research, focusing on the analysis of LEAP program documents, the analysis of LEAP participants' essays on leadership, and the results of interviews with 24 LEAP participants. This study aims to describe the contribution of leadership-based professional development programs to regeneration in Dompet Dhuafa, as well as to explain participants' perceptions of the LEAP program. The results revealed that the LEAP program has made a significant contribution to developing the competence and leadership skills of Dompet Dhuafa employees. The program has fostered positive career development, the development of future leaders, and the improvement of overall organizational effectiveness. In the document analysis, key findings included increased participant participation in strategic projects, increased understanding of leadership principles, and improved teamwork among Dompet Dhuafa employees. Meanwhile, interviews with LEAP participants revealed positive perceptions of the program, with participants highlighting the personal and professional benefits they gained from LEAP. The research emphasizes that leadership-based professional development programs such as LEAP can be an effective tool in preparing competent and qualified cadres for non-profit organizations. With a focus on developing leadership competencies, such programs can enhance an organization's capacity to achieve its goals and provide long-term benefits to participants and the organizations they serve themselves as leaders and help LEAP participants grow into future leaders of Dompet Dhuafa.